Narrativas (auto)biográficas e significações imaginárias de educadores do Instituto Federal de Educação, Ciência e Tecnologia Farroupilha: formação estética em foco - Zanini, Rejane (2025)
This research is part of the Graduate Program in Education at the Federal University of Santa Maria (UFSM), Research Line 1: Teaching, Knowledge, and Professional Development. As a doctoral thesis, it considers the existence of an alternative perception of teacher education that emerges from the (auto)biographical narratives of the Co-Authors — a proposal that goes beyond technical, technological, and scientific dimensions, encompassing the integrality of subjects and producing a singular and plural self-composition. The general objective was to activate imaginaries in order to approach an understanding of the meanings and significations produced concerning teaching practices, inspired by the research-formation approach of Josso (2010b). The formative trajectories of six teachers were examined to identify their imaginary significations, grounded in Cornelius Castoriadis’s theory of the Social Imaginary (1987, 1999, 2004). From this foundation and within the theoretical fields involved, the study proposes the concepts of Docentitarian and Discentitarian (Auto)biographical Narratives. Specific objectives include: recognizing the subject implicated in the research; presenting the specificities and implications of teaching practice within the institution; and, based on the encounters, identifying possibilities for broadening and/or instituting new formative pathways. The study is justified by the conviction that aesthetic formation can profoundly impact both life and education, acknowledging the dynamic interrelation between education and the lives of individuals. An education that incorporates aesthetic formation approaches an integral education and opens space for sensitive formation and expanding one’s understanding of self and world (Hermann, 2010; Hillman, 2010). Moreover, the research points to the institutional potential for actions that move toward a more humanized education, as follows: the (auto)biographical narratives are, to some extent, already embedded in the formative contexts of most participants. Aesthetic formation appeared through the integration of art into the teachers’ lives, which emerges as a vital element, inseparable from the constitution of being and doing, functioning as a catalyst, as a form of self-care, care for others, and care for the world. The narratives were perceived as vectors of both pain and joy; positive and negative manifestations regarding life events appeared as marks rooted in childhood. Belonging to the institution represents a personal achievement. Teaching at IFFar requires knowledge beyond one’s specific area of expertise, generating questioning and reconstruction processes. Other transitions, such as motherhood, also intersect with teaching, shaping perceptions of self as a constitutive and existential process. The teachers’ reflections revealed an awareness of their roles within academia and scientific practice — contexts in which women face differentiation and must negotiate their choices. Regarding the institution, the participants suggested the creation of mechanisms to strengthen communication among campuses and peers, emphasizing not only personal recognition but also the institutional reinforcement of fragile areas. Thinking transdisciplinarily and inclusively may represent a viable path forward, allowing actions already in place to transcend classroom boundaries and become part of everyday institutional life.